Analisis Pengaruh Hambatan Samping Terhadap Derajat Kejenuhan Ruas Jalan Tamalanrea Raya Makassar - Yous Rizal Bombing; Robert Mangontan; Olan Jujun Sanggaria (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
The city of Makassar is one of the metropolitan cities in Indonesia which has a fairly dense population, because the population is increasing rapidly, so that it has an effect on increasing congestion in the region due to the increasing need for community mobility to support goods distribution needs. social, religious and others. This study aims to find out how the side barriers and the effect of side barriers on the degree of saturation on the left and right lanes of Jalan Tamalanrea Raya Makassar starting from the front of Putra Naga Mas BTP Store to the front of Indomart BTP Blok A 24. The data used are primary and secondary data. , then data processing was carried out with reference to the 2014 Indonesian Road Capacity Guidelines (PKJI). Based on calculations and data analysis for 3 days of observation in the study area, the highest peak traffic flow was above 1300 cur/hour. For the side obstacles that occur during peak hours on the left and right lanes are above the number of 360 incidents so that they can be classified in the medium side obstacle class, the degree of saturation of the left lane and the right lane at peak hours of traffic flow obtains a degree of saturation value of 0.51 on the right lane and 0.48 on the left lane, so it can be said that the side barriers also affect the occurrence of congestion at the location that is used as the study area.